Estudantes na Cidade Universitária - Artur Pinto
1-Maria José Belbute; 2-Maria João Gerardo; 3-Orlanda (?) (Letras); 4-Mike (?); 5-João Portilheiro; 6-Maria Otilia; 7-Artur Pinto; 8-Conceição Jordão; 9-Alberto Mendonça Neves (Medicina).